Testing Dynamic Specification of Factor Demand Equations for U.S. Manufacturing - Friesen, Jane (The Review of Economics and Statistics, 1992)
This paper addresses the question of dynamic specification of empirical models of factor demand for annual U.S. manufacturing data from 1947 to 1981. Frequently used models that treat a subset of factors as variable are shown to be misspecified. An error-correction model is considered as an alternative specification. This model is shown to dominate several more parsimonious models in several respects. However, like the other models considered, the error-correction model is unable to generate satisfactory estimates of long-run elasticities. The issue of dynamic specification remains unresolved. Copyright 1992 by MIT Press.